serum IgA, IgG, IgM levels, total protein (TP) , albumin (ALB) changes in Elderly Hip Fracture Patients After Surgery and Nutritional Support: serum IgA, IgG, IgM levels, total protein (TP) , albumin (ALB) changes - Zhang, Qin (Journal of Medical Biochemistry, 2025)
Aim: Nutritional support combined with stratified nursing under delirium risk assessment reduced postoperative delirium and improved outcomes in elderly hip fracture patients. Methods:A total of 112 patients were divided into control and study groups. The study group received stratified nursing along with enteral nutrition, while the control group received routine nursing and a normal diet. serum IgA, IgG, IgM levels, total protein (TP) , albumin (ALB) changes were evaluated. Results: Compared to the control group, the study group had shorter postoperative bed rest and hospital stays, and lower incidences of delirium and adverse events. The study group also showed reduced depression and anxiety scores, increased levels of hemoglobin, albumin, and total protein, elevated levels of immunoglobulins A, M, and G, better sleep quality, and lower pain scores postoperatively. Nursing satisfaction was higher in the study group. Conclusion: Nutritional support and stratified nursing improved immune function and reduced delirium in elderly hip fracture patient’s post-surgery.